A Randomized Trial to Evaluate the Effects of Folic Acid and Zinc Supplementation on Male Fertility and Livebirth: Design and Baseline Characteristics. Issue 1 (12th November 2019) - Schisterman, Enrique F; Clemons, Traci; Peterson, C Matthew; Johnstone, Erica; Hammoud, Ahmad O; Lamb, Denise; Carrell, Douglas T; Perkins, Neil J; Sjaarda, Lindsey A; Van Voorhis, Bradley J; Ryan, Ginny; Summers, Karen; et al.
Abstract: The Folic Acid and Zinc Supplementation Trial (FAZST) was a multicenter, double-blind, block-randomized, placebo-controlled trial to determine whether folic acid and zinc supplementation in men improves semen quality and increases livebirth rate among couples seeking infertility treatment (2013–2017). Eligible men were aged 18 years or older with female partners aged 18–45 years, seeking infertility treatment. Men were randomized (1:1) to 5 mg folic acid and 30 mg elemental zinc daily or matching placebo for 6 months. Randomization was stratified by site and intended infertility treatment (in vitro fertilization (IVF), non-IVF/study site, and non-IVF/outside clinic). Follow-up of men continued for 6 months, and female partners were passively followed for a minimum of 9 months. Women who conceived were followed throughout pregnancy. Overall, 2, 370 men were randomized during 2013–2017 (1, 185 folic acid and zinc, 1, 185 placebo); they had a mean age of 33 years and body mass index (weight (kg)/height (m) 2 ) of 29.8. Most participants were white (82%), well educated (83% with some college), and employed (72%). Participant characteristics were balanced across intervention arms. Study visits were completed by 89%, 77%, and 75% of men at months 2, 4, and 6, respectively. Here we describe the study design, recruitment, data collection, lessons learned, and baseline participant characteristics.